2013
DOI: 10.1088/0022-3727/46/50/505501
|View full text |Cite
|
Sign up to set email alerts
|

Improving sensitivity of piezoresistive microcantilever biosensors using stress concentration region designs

Abstract: To improve the surface-stress sensitivity of piezoresistive microcantilever biosensors, this study presents cantilever designs with circular, square and triangular stress concentration regions (SCRs). The cantilever substrates are made of silicon and silicon dioxide and the piezoresistor is p-doped silicon. The cantilevers are characterized using FEM software for their surface-stress sensitivity and thermal vulnerability by applying surface stress, temperature and bias voltage loads. A relation for the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In this regard, static mode of measurement has advantages in terms of reduced dependency of measurement on external ambient and intrinsic material parameters, and better performance in liquid medium which is desirable for chemical and biological sensing applications. When operated in static mode with self-sensing piezoresistive readout, the performance of cantilever can be improved by incorporating stress concentration regions [ 89 92 ]. The stress concentration regions (SCRs) act as mechanical amplifiers of stress generated due to cantilever bending, thereby improving electrical sensitivity.…”
Section: Sensing Modesmentioning
confidence: 99%
“…In this regard, static mode of measurement has advantages in terms of reduced dependency of measurement on external ambient and intrinsic material parameters, and better performance in liquid medium which is desirable for chemical and biological sensing applications. When operated in static mode with self-sensing piezoresistive readout, the performance of cantilever can be improved by incorporating stress concentration regions [ 89 92 ]. The stress concentration regions (SCRs) act as mechanical amplifiers of stress generated due to cantilever bending, thereby improving electrical sensitivity.…”
Section: Sensing Modesmentioning
confidence: 99%
“…A series of studies have found that in contrast to the design of force-sensing cantilevers where a high-aspect-ratio design is preferred, surface stress sensing, in general, prefers a lowaspect-ratio geometry. 14) Moreover, designs with novel features such as vertically connected cantilevers, 15) cantilever arrays, 16) double-sided coating, 17) and stress-concentrating holes 18) are found to be effective in improving sensitivity. While these studies provide valuable insights, their scopes are limited as they focus exclusively on cantilevers with basic shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoresistors are the simplest form of piezoresistive devices with several advantages: low cost, small size, low phase lag, and extensive dynamic range [14]. Besides, the main attractive features of piezoresistive sensors are their high sensitivity and selfsensing ability [15], which become indispensable for detecting low mass concentrations such as chemical, biochemical, and biological analytes.…”
Section: Introductionmentioning
confidence: 99%